KEKERABATAN BAHASA JAWA DAN BAHASA MADURA DALAM KAJIAN LINGUISTIK HISTORIS KOMPARATIF - Tantri, Afitta; Saddhono, Kundharu; Mulyono, Slamet (DIALEKTIKA JURNAL PENDIDIKAN BAHASA INDONESIA, 2024)
Indonesia is a country that has a variety of regional languages. Language itself is an important thing in human life. Javanese and Madurese are two different languages that are closely related. This research will discuss the relationship between Javanese and Madurese languages. The research method to determine the level of relationship between the two languages is to use a qualitative descriptive method with lexicostatistical data analysis techniques. This analysis focuses on Javanese and Madurese vocabulary which are related. With 200 pairs of Swadesh vocabulary words studied from Javanese and Madurese. From the research carried out, the results showed that the kinship relationship between Javanese and Madurese is 25%, where according to the table of kinship levels the two languages are still categorized as cognate. Keywords: Javanese, Madurese, comparative historical linguistics